Teaching Hispanic Culture, Diversity, and Tolerance through Hispanic Dances and Music: Two Approaches for Flamenco & Caribbean Dances - Espino-Bravo, Chita; English, Nicole (Revista de Investigación sobre Flamenco "La madrugá", 2024)
A Sociology Approach: Dance can be a useful tool for teaching students about culture and community. Through the language of Dance and Music (Caribbean Dance), context is given to social facts, which engages and informs students about such social issues as history, Colonialism, social class, gender, race/ethnicity, and social justice. The added bonus of using Dance as a lens is that it involves active, embodied learning (Dewey, English, Mead), making the material more memorable, meaningful, and relevant to the learner. A Communicative Approach (Task-based Learning Activity) & Language for Specific Purposes: Task-Based Language Teaching (TBLT) is a derivative of the Communicative Approach (CA) and Second language Acquisition (SLA) studies. Certain types of communicative learning activities can lead to acquisition of language (Abdel Kazeroni, Aquilino Sanchez, Margaret Robertson, Yiqng Lin). When teaching a Hispanic Dance Session using specific Spanish vocabulary of the dance to address certain dance movements (like Flamenco dance), we engage language learners in acquiring Spanish parts of language related to the flamenco dance. We also immerse learners in the culture of flamenco dance, and its rich cultural context, so they can learn about the social context, gender issues, the different meanings of the dance movements, the metaphors, and by extension they will learn about diversity, tolerance, inclusion, and respect for another culture through dance and music (Language for Specific Purposes: Angela N. Gardner, Howard Gardner, Victoria Escaip).